Patterns of flow pressure due to hand-water-interaction of skilled breaststroke swimmers - a preliminary study - Ungerechts, B. E.; Cesarini, D.; Hamann, M.; Ritter, Y.; Weidner, S.; Haldorn, T.; Hermann, T. (Procedia Engineering, 2016)
Self-induced aquatic propulsion is an effect of interaction of the limbs and water mass (LWI) which change the energy-density per volume and the momentum of water mass, simultaneously. The change of volumetric energy-density of water can be measured via pressure tap probes detecting static pressure of unsteady flow via pressure sensors. The data of elite breaststroke swimmers wearing gloves with pressure taps on both sides of the hands were presented as pressure difference per hand (p-diff) in real-time in a split screen video together with the hand action. The purpose of this preliminary study was to check a) the stability of the setup including the data collection under pool condition with various swimmers and b) to answer coaches' questions concerning the relation of peak pdiff-data and hand action. Among others it is shown that p-diff(max) coincides with a) deepest hand penetration at the end of the inward sweep of the hands and b) max body acceleration during hand action, shortly before max body velocity occurs.